HUBUNGAN PANJANG TUNGKAI DAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN PENALTY - Cahyo Pratomo; Aditya Gumantan (Journal of Physical Education, 2020)
This reseach study is aimed to investigate leg length and leg power towards penalty kick result of Universitas Teknokrat Indonesia’s students majoring in Physical Education batch 2019. Moreover, this study is intended to figure out the impact of leg length and leg power towards penalty kick result. The method used in this study is a descriptive correlational method by having 20 students as a sample of the analysis. The result of this study shows that the correlation between leg length and the accuracy of penalty kick is 56,25% and the value of correlational coefficient between leg strength and penalty kick result is 67,24%. From these two variables, the biggest contribution of penalty kick result comes from the leg strength with the percentage of 67,24%.Keywords: limbs, power limbs, strength, penalty, football